1991
DOI: 10.1161/01.res.68.3.662
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal maturation of excitation-contraction coupling in rat ventricle in relation to the subcellular localization and surface density of 1,4-dihydropyridine and ryanodine receptors.

Abstract: To better understand excitation-contraction coupling in cardiac muscle, we investigated the main Ca2+ channels involved in that process in adult and neonatal rat ventricle. Voltage-dependent (L-type) Ca2+ channels and sarcoplasmic reticulum Ca2+ release channels were labeled by means of [3H] (+)-PN200-110 and [3H]ryanodine, respectively. The number of [3H]ryanodine binding sites (per gram tissue) increased more than that of [3H] (+)-PN200-110 binding sites over the postnatal period (2.1-fold versus 1.35-fold, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(62 citation statements)
references
References 48 publications
5
53
0
2
Order By: Relevance
“…These results indicate that the functional role of Ca 2+ release from the SR increases during development. Similar developmental increases in inotropic sensitivity to ryanodine have been observed in the postnatal rat (14,15), rabbit (16), late fetal guinea pig (17), and middle age chick embryo (18), and also in the postnatal mouse (3). In the mouse ventricle, the present results revealed that, large changes in the inotropic responses to nifedipine and ryanodine occurs during the late fetal period and during the second postnatal week (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…These results indicate that the functional role of Ca 2+ release from the SR increases during development. Similar developmental increases in inotropic sensitivity to ryanodine have been observed in the postnatal rat (14,15), rabbit (16), late fetal guinea pig (17), and middle age chick embryo (18), and also in the postnatal mouse (3). In the mouse ventricle, the present results revealed that, large changes in the inotropic responses to nifedipine and ryanodine occurs during the late fetal period and during the second postnatal week (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…The rapid increase in Ca¥ concentration at the restricted space between the T_tubular and junctional SR membranes during the initial phase of excitation-contraction coupling may allow activation of various Ca¥ sensitive processes in that region when the Ca¥ concentration around the contractile proteins is still low. In the mammalian ventricular myocardium, the dihydropyridine binding sites (L-type Ca¥ channels; Wibo, Bravo & Godfraind, 1991), as well as the Na¤-Ca¥ exchanger (Frank, Mottino Reid Molday & Philipson, 1992;Chen, Mottino, Klitzner, Philipson & Frank, 1995), are reported to be localized along the T-tubules. Rapid inactivation of the trans-sarcolemmal Ca¥ influx through L_type Ca¥ channels and activation of inward current via the Na¤-Ca¥ exchange system could be explained by rapid increase in Ca¥ concentration in the restricted area (AdachiAkahane, Cleeman & Morad, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Excitationcontraction coupling in neonatal cardiomyocytes appears to be regulated by Ca 2ϩ influx through the sarcolemma, with the L-type Ca 2ϩ channel being the main source for trans-sarcolemmal Ca 2ϩ flux (2,7,14,34,55). However, although RyRs are functional in neonatal cardiomyocytes, Ry only reduces Ca 2ϩ transients by ϳ15% in the day 1 neonatal rat heart versus 88% in juvenile cardiomyocytes, suggesting an increased reliance on RyR as a function of age (10,11).…”
Section: Ryr Camentioning
confidence: 99%